Generalized wave-domain transforms for listening room equalization with azimuthally irregularly spaced loudspeaker arrays - Hofmann, Christian; Kellermann, Walter (IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2016)
In reverberant environments, Listening Room Equalization (LRE) by pre-filtering of loudspeaker signals is highly desirable for premium sound reproduction systems with a high number of loudspeakers. In this contribution, the efficient concept of LRE by wave-domain adaptive filtering is extended by deriving generalized loudspeaker signal transforms for loudspeaker arrays with an irregular azimuthal spacing. In particular, a matrix approximation allows to restore the unitarity property of a transform matrix which lost the unitarity when applied to irregular arrays instead of regular ones. Simulations of adaptive LRE systems with irregular loudspeaker arrays confirm the efficacy of the proposed, novel, generalized transform
Keywords: WDAF; Wave Domain; Azimuthally Irregular Arrays; Spatial Transforms; Equalization